A Case of Bedside Ultrasound in COVID-19 to Prognosticate Functional Lung Recovery. (25th January 2021) - Bartlett, Kathryn B.; Laubach, Lexis T.; Evans, Elizabeth M.; Roth, Kevin R.
Abstract : Introduction . The fight against COVID-19 poses questions as to the clinical presentation, course, diagnosis, and treatment of the condition. This case study presents a patient infected with COVID-19 and suggests with additional research, that bedside ultrasound may be used to diagnose severity of disease and potentially, prognosticate functional lung recovery without using unnecessary resources and exposing additional healthcare professionals to infection. Case Report . A 46-year-old male presented to the emergency department (ED) with cough, fever, and shortness of breath. Chest X-ray showed patchy airspace opacities bilaterally. Rapid testing resulted positive for SARS-CoV-2. Bedside ultrasound showed abnormal lung parenchyma, with diffuse comet tail artifacts, consistent with interstitial pulmonary edema. Following a prolonged intubation, patient's abnormal lung ultrasound findings are resolved.